Réponses

2014-01-26T15:11:57+01:00
2) E= (3x-2)(3x-2)-(3x-2)(x-7)
    E= 9x²-6x-6x-(3x²-21x-2x-5)
    E= 9x²-6x-6x-4-3x²+21x+2x+5
    E= 6x²11x+1

3) E= (3x-2)(3x-2)-(3x-2)(x-7)
    E= (3x-2)[(3x-2)-(x-7)]
    E= (3x-2)(3x-2-x-7)
    E= (3x-2)(2x-9)

4) E= (3(1sur2)-2)(3(1sur2)-2)-(3(1sur2)-2)(1sur2)-7)
    E= (1.5-2)(1.5-2)-(1.5-2)((1sur2)-7)
    E= 0.5*0.5*0.5*(-6.5)
    E= -0.8125
pour le 4 je ne suis pas sûr

5) (3x-2)(2x-5)=0
3x-2=0 ou 2x-5=0
3x=2    ou 2x=5
x=2sur3 ou x= 5sur2

voila il n'y a que le 4 que je suis pas sûr bon courage :)